Church and religious situation in the Ukraine: Trends 2019 - request for extension of questionnaires for sociological surveys - Oksana Horkusha (Релігійна свобода, 2020)
Recently the Razumkov Center published new sociological data “State and Church in Ukraine - 2019: results of the year and prospects of relations development” and organized a round table on “Religion and power in Ukraine: problems of relations”. This sociological data is an extremely important fixation of the empirical indicators of the religious situation in contemporary Ukraine. Analyzing them, we can see a clear correlation between faith, religious and church affiliation, and the experience and position of those interviewed. However, for further in-depth understanding of how religious and denominational identity and church affiliation correlate with event experience, prevailing historiographical discourse, life position, and civic consciousness, it would be worthwhile to expand the questionnaires. Undoubtedly, religion is a significant factor in shaping Ukraine's future. Especially the influence of church affiliation on social reality is noticeable in the situation of armed aggression against Ukraine of the Russian Federation, which does not neglect to use as a weapon in the information war a religious sermon in the temples of the subordinate Moscow center of the church. That is why it is so important to systematically monitor the correlation of religious and ecclesiastical affiliations with world-view parameters and real events in the context of which transformations of the religious situation and socio-state-church relations take place.Current trends in religious change clearly include factors that are reflected in sociological research (such as a decline in the Church's recognition of moral authority is an indication of the spread and affirmation of secular tendencies and the activation of secular ideology in conjunction with cultural and world-view circumstances of the Church. and confessions turned out to be unsolicited, irrelevant, ineffective, incompetent, etc.) and factors that went unaddressed due to the fact that previous questionnaires did not contain questions that Anish not issued to date. Therefore, it is time to complete the questionnaires to explain the jumps unexpected in terms of previous sociological data.